Relationship between stunting status and parental parenting patterns with the incidence of dental caries in toddlers in the working area of the bugel public health center - Herningrum Dessylindra; Munaya Fauziah; Dewi Purnamawati; Dihartawan Dihartawan (Science Midwifery, 2026)
Stunting and dental caries are two common child health problems that often occur simultaneously and influence each other. Parental care patterns, education level, knowledge, and socioeconomic status play important roles in dental caries occurrence in stunted children. To analyze the relationship between stunting status and parental care patterns with dental caries occurrence in children under five, as well as the factors underlying dental caries. Cross-sectional study on 162 children under five (81 stunted and 81 normal) at Bugel Public Health Center. Data collected through questionnaires and examinations. Analysis used Chi-Square test and multiple logistic regression (α=0.05). Prevalence of stunting and caries were each 90.1%. Significant relationships found between stunting and caries (p=0.001; OR=17.25), parental care and caries (p=0.002; OR=18.61), education and caries (p=0.035; OR=4.42), knowledge and caries (p=0.047; OR=4.30). Socioeconomic status was not significantly associated (p=0.433). Multivariate analysis showed stunting (OR=5.59; p=0.032) and parental care (OR=4.80; p=0.040) as significant factors. Stunting status and parental care are significant factors of dental caries in children under five. Integrated intervention programs are needed to address stunting and dental health, parenting education, and routine monitoring.